Development of environment friendly water-based self-rechargeable battery. (July 2021) - Karmakar, Srikanta; Pramanik, Ashim; Kumbhakar, Partha; Sarkar, Rajat; Kumbhakar, Pathik
Abstract: There is a growing demand for the development of sustainable electrical energy generation devices with a high energy-to-price ratio. On the other hand, industrial waste, such as fly ash is a hazard to environmental pollution. However, here for the first time, water-based self-rechargeable batteries have been fabricated by using bio-waste (golden shower tree bark ash (TBA)), a rural pollutant (cow dung ash), and industrial pollutant (coal fly ash). The TBA-based battery, out of all three batteries, shows the highest open-circuit voltage of ∼1.48 V and a specific capacity of 183 mAhg −1 . Further, the TBA based cell has retained ∼97% columbic efficiency even after 2000 cycles. It has been found that pH of TBA ash is the highest, i.e. ∼12 in presences of tap water and it is found that the TBA ash is composed of a large number of metal oxides. The materials present in the ash powder have generated oxides and hydroxides ions which have, in turn, caused the generation of the potential difference between the two electrodes. The fabricated devices are portable and can power up a large number of electronic gadgets, including light-emitting diodes (LEDs). It is envisioned that this work may open the door to the development of sustainable, environment-friendly, and low-cost bio-waste ash-based self-rechargeable energy devices in future. Graphical abstract: Environment friendly self-rechargeable water-based bio-waste ash battery. Image 1 Highlights: Fabrication of commercial electrolyte free, bio-waste based self-rechargeable batteries. The TBA based battery shows the highest open-circuit voltage of ∼1.45 V. The TBA-based cell shows the highest specific capacity of 183 mAhg −1 . The TBA-based battery has retained of 97% columbic efficiency even after 2000 cycles.